Educating for Sustainability: Perspectives and Critical Notes on Accounting Scholars’ Role in Higher Education - del Baldo Mara; Baldarelli Maria-Gabriella (Scientific Annals of Economics and Business, 2017)
Education for sustainable development represents a relevant issue that allows Universities to lead and respond to social needs towards a more sustainable life and a complete change in the global paradigm of education and involvement of society. A crucial point for developing a culturally sensitive vision is to deepen the scholars’ genuine commitment to sustainability. A pillar of sustainability education should rest on authenticity, intended as coherence between the scholars’ research and teaching arguments relative to sustainability and the concrete behaviors held in their professional and personal spheres of life. Starting from this premise, the papers aims to inquire if there is a decoupling between the concepts scholars contribute to promote within the sustainability discourse and the real practice of sustainability in their personal and professional experience. “Is there a missing link between what scholars teach and study, thereby contributing to sustainability research and their daily choices and style of life?” After having presented the research design and the methodological approach adopted to empirically investigate the phenomenon the attention has been focused on the social and environmental accounting research literature, where some contributions claim for the presence of “blue meanies” that invade the world of scholarship, reflection, collegiality and hinder the development of challenges toward sustainability. The preliminary results of the explorative study suggest that a lot of tension related to education for sustainability improve the transfer of sustainable values and attitudes within the scientific community and the students, while several factors hinder sustainable behaviors in the daily professional and personal life of scholars, thus undermining relationships which are a pillar of sustainability.